Molecular diet analysis in mussels and other metazoan filter feeders and an assessment of their utility as natural eDNA samplers. (12th October 2022) - Weber, Sven; Junk, Isabelle; Brink, Lukas; Wörner, Manuel; Künzel, Sven; Veith, Michael; Teubner, Diana; Klein, Roland; Paulus, Martin; Krehenwinkel, Henrik
Abstract: Molecular gut content analysis is a popular tool to study food web interactions and has recently been suggested as an alternative source for DNA‐based biomonitoring. However, the overabundant consumer's DNA often outcompetes that of its diet during PCR. Lineage‐specific primers are an efficient means to reduce consumer amplification while retaining broad specificity for dietary taxa. Here, we designed an amplicon sequencing assay to monitor the eukaryotic diet of mussels and other metazoan filter feeders and explore the utility of mussels as natural eDNA samplers to monitor planktonic communities. We designed several lineage‐specific rDNA primers with broad taxonomic suitability for eukaryotes. The primers were tested using DNA extracts of different limnic and marine mussel species and the results compared to eDNA water samples collected next to the mussel colonies. In addition, we analysed several 25‐year time series samples of mussels from German rivers. Our primer sets efficiently prevent the amplification of mussels and other metazoans. The recovered DNA reflects a broad dietary preference across the eukaryotic tree of life and considerable taxonomic overlap with filtered water samples. We also show the utility of a reversed version of our primers, which prevents amplification of nonmetazoan taxa from complex eukaryote community samples, by enriching fauna associated with the marine brown algae Fucus vesiculosus . Our protocol will enable large‐scale dietary analysis in metazoan filter feeders, facilitate aquatic food web analysis and allow surveying of aquacultures for pathogens. Moreover, we show that mussels and other aquatic filter feeders can serve as complementary DNA source for biomonitoring.